Internet of Things for Mechanical Engineers - Soni, Dr. Tukesh (Internet of Things for Mechanical Engineers, Edition 1, 2024)
The Internet of Things (IoT) is rapidly transforming the landscape of mechanical engineering, creating opportunities for smarter, more connected, and efficient systems. What once relied on manual oversight and scheduled maintenance now thrives on real-time data, predictive analytics, and automation. Mechanical engineers, traditionally focused on the physical properties of machines, must now integrate digital technologies into their designs, processes, and operations. This book, "Internet of Things for Mechanical Engineers," is designed to bridge the gap between the world of traditional mechanical engineering and the ever-evolving IoT landscape. As IoT technologies continue to revolutionize industries like manufacturing, robotics, and automation, it is crucial for engineers to understand the fundamentals of IoT and how these technologies can be applied to mechanical systems. Throughout the book, we delve into the core principles of IoT, starting with the basics of sensors, actuators, and data acquisition. From there, we explore the communication protocols and data processing methods that allow IoT devices to interact seamlessly across networks. Practical applications such as smart manufacturing, predictive maintenance, and robotics are discussed in detail, providing real-world examples of how IoT is reshaping mechanical engineering. We also address the security and privacy challenges associated with IoT systems, ensuring that engineers are equipped to handle the complexities of modern digital infrastructure. What sets this book apart is its focus on the practical applications of IoT for mechanical engineers. While the technological underpinnings of IoT are complex, we present the material in a clear and accessible way, with numerous diagrams, tables, and real-world case studies to illustrate key concepts. Whether you are an experienced engineer looking to expand your skill set or a student preparing for a future in a rapidly changing industry, this book will provide the knowledge and tools needed to navigate the intersection of IoT and mechanical systems. As we move further into the era of Industry 4.0, the integration of IoT into mechanical engineering will become not just an advantage but a necessity. We hope this book will serve as a valuable resource for engineers seeking to harness the power of IoT and unlock new possibilities in their work.